Pengaruh Struktur Kepemilikan, Good Corporate Governance, dan Ukuran Perusahaan terhadap Kualitas Laba - Syafianti, Naila Sakinah; Anwar Hariyono (Journal of Culture Accounting and Auditing, 2026)
This study investigates the effects of ownership structure, Good Corporate Governance (GCG), and firm size on earnings quality among financial sector firms listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. Using a quantitative design and multiple linear regression, the research analyzes 140 observations derived from 35 purposively selected companies. The findings reveal that ownership structure and GCG do not exhibit significant influences on earnings quality, whereas firm size demonstrates a positive and significant impact. When examined collectively, all variables exert a significant effect, with firm size emerging as the most influential determinant. These results imply that larger firms tend to report higher-quality earnings. The study’s scope limited to a short observation window and a single industry may constrain the broader applicability of its conclusions across other sectors in Indonesia.